Safety and efficacy of monthly high-dose vitamin D3 supplementation in children and adolescents with sickle cell disease - Hanna, Diana; Kamal, Doaa E.; Fawzy, Hebatallah M.; Abd Elkhalek, Reham (European journal of pediatrics, 2024)
Little is known about the impact of vitamin D supplementation on hand grip strength (HGS) and health-related quality of life (HRQoL) in children and adolescents with sickle cell disease (SCD). We aimed to evaluate the safety and efficacy of monthly high-dose vitamin D 3 supplementation and its implications on bone mineral density (BMD), HGS, and HRQoL in patients with SCD and healthy controls. The study included 42 children with SCD and 42 healthy matched controls. The study participants were supplemented with high-dose monthly oral vitamin D 3 . Changes in the serum level of 25(OH) vitamin D 3 , maximum HGS, and BMD from baseline to 6 months were assessed, and the HRQoL questionnaire and Childhood Health Assessment Questionnaire (CHAQ) were used to evaluate the functional capacity. At baseline, SCD subjects had poorer growth status indicated by negative Z scores. Suboptimal BMD was detected by significantly lower Z score, and lower HGS and worse HRQL parameters were found compared to the controls ( P < 0.001). Median 25(OH) vitamin D 3 was significantly lower in SCD patients compared to controls (16.5 vs. 28 ng/mL, respectively ( P < 0.001)). After 6 months of vitamin D supplementation, there was significant improvement in the DEXA Z -score ( P < 0.001), limitation of physical health ( P = 0.02), pain scores ( P < 0.001), and CHAQ grades ( P = 0.01) in SCD patients. A significant improvement in HGS ( P < 0.001 and P = 0.005) as well as the CHAQ score ( P < 0.001 and P = 0.003) was detected in the SCD group and controls, respectively. There were no reported clinical adverse events (AEs) or new concomitant medications (CMs) during the study duration, and safe levels of Ca and 25 (OH) D3 were observed at 3 and 6 months for both groups. There was a significant positive correlation between HGS and total physical score ( r = 0.831, P < 0.001) and a negative correlation with CHAQ score ( r =  − 0.685, P < 0.001). We also detected a significant positive correlation between vitamin D levels at 6 months and HGS ( r = 0.584, P < 0.001), pain score ( r = 0.446, P < 0.001), and a negative correlation with CHAQ score ( r =  − 0.399, P < 0.001).